The curious case of COVID-19: Its murky origin, negligence and a botched international attempt for a cover-up - Dhar, Ruby; Pethusamy, Karthikeyan; Talukdar, Joyeeta; Karmakar, Abhibrato; Kumar, Arun; Karmakar, Subhradip (Asian Journal of Medical Sciences, 2021)
COVD-19 caused due to SARS-CoV2, family of Coronaviridae, the order Nidovirales, and the genus Coronavirus. A zoonotic spillover infection from bats to humans through some intermediate host was proposed to be responsible for its origin. This theory gained traction and raised no concern because our experience with other pathogenic viruses with humans in the past followed a similar trajectory. However, what caught the attention are few missing pieces of the jigsaw puzzle that seems to defy logic. A detailed investigation revealed a trail of deception, negligence, and blotched attempt of cover-up.